Penyusunan Indeks Karya Intelektual Minangkabau di Dinas Perpustakaan dan Kearsipan Kota Padang Panjang - Pratiwi Devitasari; Malta Nelisa (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe study of this research in about preparation a index of Minangkabau intellectual works collection in libraries and archives of Padang Panjang city. The purpose is to describe about preparation a index of Minangkabau intellectual works collection. This research has been done by a descriptive method by visiting directly to libraries and archives of Padang Panjang city. After the data analyzed, the conclusion explains some steps of preparation a index of Minangkabau intellectual works collection: (1) preliminary observations; (2) selecting collections; (3) recording collection descriptions; (4) create annotations (5) create keywods; (6) indexing; (7) typing index.Keywords: index, annotations, Minangkabau